Construction of indicator system and comprehensive evaluation of high-quality development of cultural tourism integration in revolutionary base areas - Ping Li; Chunxiao Xu; Huiting Liang (PLoS ONE, 2026)
Clarifying the conceptual framework of high-quality development in cultural-tourism integration and establishing a corresponding evaluation system suitable for county-level regions in revolutionary base areas are crucial for revitalizing these regions in the new era. Guided by national strategies, informed by local practices, and tailored to the regional characteristics of revolutionary base areas, this study employs a mixed-method approach combining grounded theory and expert consultation to develop a scientifically robust evaluation indicator system for county-level high-quality development in cultural-tourism integration. Using the Former Central Soviet Area of Jiangxi-Fujian-Guangdong as a case study, the research reveals three key findings: 1) The core connotation of high-quality development in cultural-tourism integration in revolutionary base areas centers on leveraging tourism activities rooted in red culture to drive cross-sector industrial integration, thereby enhancing the level, quality, and sustainability of economic and social development. 2) The evaluation indicator system comprises 21 indicators organized into three dimensions: development elements, development effects, and development environment. 3) The high-quality development level of cultural-tourism integration in the Former Central Soviet Area demonstrates a fluctuating upward trend over time. Spatially, low-level areas show contraction while high-level areas expand, accompanied by a gradually intensifying trend of spatial agglomeration.